Affective and physiological correlates of the perception of unimodal and bimodal emotional stimuli - Rosa, P. J. (2018)
Background: Despite the multisensory nature of perception, previous research on emotions has been focused on unimodal emotional cues with visual stimuli. To the best of our knowledge, there is no evidence on the extent to which incongruent emotional cues from visual and auditory sensory channels affect pupil size. Aims: To investigate the effects of audiovisual emotional information perception on the physiological and affective response, but also to determine the impact of mismatched cues in emotional perception on these physiological indexes. Method: Pupil size, electrodermal activity and affective subjective responses were recorded while 30 participants were exposed to visual and auditory stimuli with varied emotional content in three different experimental conditions: pictures and sounds presented alone (unimodal), emotionally matched audio-visual stimuli (bimodal congruent) and emotionally mismatched audio-visual stimuli (bimodal incongruent). Results: The data revealed no effect of emotional incongruence on physiological and affective responses. On the other hand, pupil size covaried with skin conductance response (SCR), but the subjective experience was partially dissociated from autonomic responses. Conclusion: Emotional stimuli are able to trigger physiological responses regardless of valence, sensory modality or level of emotional congruence.